Critical Factors Affecting the Participation in COVID-19 Vaccination Program in Residency of Surakarta: The Extended Theory of Planned Behaviour - Bayu Sindhu Raharja; Dewi Hambar Sari (Journal of Theoretical and Applied Management (Jurnal Manajemen Teori dan Terapan), 2022)
Objective: This study evaluates the critical factors affecting COVID-19 vaccine acceptance in Indonesia using a proposed extended theory of planned behaviour (extended-TPB). Design/Methods/Approach: We conducted an online survey (N = 222 respondents) using a valid and reliable questionnaire to evaluate people's intention to take the COVID-19 vaccination. A structural equation modeling was performed to demonstrate the impact of religious acceptance (RA), vaccine safety (SF), trust (TS), perceived behavioural control (PBC), attitude towards vaccination (ATT), and subjective norms (SN), on intention (IN) to accept COVID-19 vaccine. Findings: The results show positive relationships of all hypotheses except the correlation between RA and TS. TS becomes a positive determinant of ATT, SN, PBC, and INT, and TS is influenced by SF but not by RA. TS is the key determinant factor of intention to uptake the COVID-19 vaccine. Originality: This study used a proposed extended TPB by adding trust, religious acceptance, and safety as additional components of TPB to predict the intention to participate in COVID-19 vaccination. This study is essential because the vaccine is believed to be the best strategy to deal with virus-related diseases, such as COVID-19. However, there is a lack of information on the multifactor effects of Indonesian people's acceptance of vaccination, especially among Surakarta residents. Practical/Policy implication: This research can be a recommendation for the Indonesian government to elevate public intention to take the COVID-19 vaccine, especially by implementing policies that accentuate people's trust by confirming and publishing information about the vaccine safety.